The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1126/science.1163382
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lived Volcanism on the Lunar Farside Revealed by SELENE Terrain Camera

Abstract: We determined model ages of mare deposits on the farside of the Moon on the basis of the crater frequency distributions in 10-meter-resolution images obtained by the Terrain Camera on SELENE (Selenological and Engineering Explorer) (Kaguya). Most mare volcanism that formed mare deposits on the lunar farside ceased at approximately 3.0 billion years ago, suggesting that mare volcanism on the Moon was markedly reduced globally during this period. However, several mare deposits at various locations on the lunar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 18 publications
7
106
1
1
Order By: Relevance
“…The derived model age of this deposit is estimated to be ∼2.7 Ga; hence, it is substantially younger than the Imbrian-Eratosthenian boundary (3.2 Ga). Haruyama et al (2009) also found that several farside maria (e.g., Apollo, Antoniadi, and the eastern part of Mare Moscoviense) formed in the Eratosthenian Period. Our result indicates that the mare basalt in Campbell is one of the mare deposits formed in the latest phase of farside volcanism.…”
Section: Campbellmentioning
confidence: 99%
See 2 more Smart Citations
“…The derived model age of this deposit is estimated to be ∼2.7 Ga; hence, it is substantially younger than the Imbrian-Eratosthenian boundary (3.2 Ga). Haruyama et al (2009) also found that several farside maria (e.g., Apollo, Antoniadi, and the eastern part of Mare Moscoviense) formed in the Eratosthenian Period. Our result indicates that the mare basalt in Campbell is one of the mare deposits formed in the latest phase of farside volcanism.…”
Section: Campbellmentioning
confidence: 99%
“…As presented by Haruyama et al (2009), comparing model ages of mare basalts on the farside and those on the nearside indicates that the timing of the termination of mare volcanism differed between the farside (∼2.5 Ga) and the nearside (∼1.2 Ga). This difference might be related to the thicker crust (e.g., Head and Wilson, 1992) and/or a deficiency of heat-producing radioactive elements on the farside (e.g., Jolliff et al, 2000).…”
Section: Comparison With the Spa Basin And The Nearsidementioning
confidence: 99%
See 1 more Smart Citation
“…The formation ages of farside mare areas were re-estimated by counting craters using high spatial resolution Terrain Camera images. Mare Moscoviense and the Antoniadi and Apollo craters in the SPA basin have been shown to have longlived volcanism to 2.5-2.6Ga compared to a previous estimation of 3.5 Ga 24) . Recently formation ages of nearside mares are also re-estimated in detailed by crater counting method.…”
Section: Dichotomy Of Nearside and Farside Of The Moonmentioning
confidence: 84%
“…Dating of Apollo and Luna basalts indicated ages ranging between 4.2 and 3.1 Ga during which large basins were filled with lava and solidified. This was taken as an evidence that the Moon has been volcanically inactive for aeons, although occasionally some younger basaltic surfaces with ages of up to~1 Ga, were found (e.g., [63][64][65][66][67]). Chandrayaan-1 results and data from other recent missions viz.…”
Section: Evidence Of Recent Volcanismmentioning
confidence: 99%